Application of an advanced real options approach for renewable energy generation projects planning - Martínez-Ceseña, E.A.; Mutale, J. (Renewable & sustainable energy reviews, 2011)
Nowadays, there is growing interest in renewable energy (RE) generation projects due to environmental and sustainability concerns. However, initial costs and uncertainties caused by RE source variability, changes in support schemes, and other factors can render RE projects unattractive when subject to conventional financial assessment. Initial research suggests that the value of RE projects can be enhanced by the application of real options (RO) theory in the planning and evaluation of such projects. Literature on application of RO planning in RE generation projects is limited, and typically focuses solely on flexible investment decisions and neglects flexible designs. A more comprehensive approach should address flexibility in designs. This paper proposes an advanced RO methodology for RE generation projects planning, and illustrates the methodology using variations of a hydropower case study. The fundamental differences between advanced RO approaches and other techniques are illustrated on a simple case study. The complete version of the proposed advanced methodology is then compared against other available tools. The results show higher expected profits for projects planned with the advanced RO methodology.